Trade Facilitation Needs and Customs Valuation in Fiji - Biman Chand Prasad (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2006)
In line with most developing countries, the last decade has seen Fiji adopt an export oriented, outward-looking approach to trade relations. Import restrictions have been largely lifted in favour of export promotion, and as such Fiji now has a more liberalized or open economy with increased volumes of both exports and imports
Keywords: F1; 330; Trade Facilitation; Customs Valuation; Fiji